Evaluation of an Early Intervention Model for Child and Adolescent Victims of Interpersonal Violence - Claudia Calvano; Elena Murray; Lea Bentz; Sascha Bos; Kathrin Reiter; Loretta Ihme; Sibylle M. Winter (MDPI AG, 2021)
Only the minority of youth exposed to traumatic events receive mental health care, as trauma-informed clinical services are lacking or are poorly accessible. In order to bridge this gap, the Outpatient Trauma Clinic (OTC) was founded, an easily accessible early, short-time intervention, with onward referral to follow-up treatment. This report presents the OTC's interventional approach and first outcome data. Using a retrospective naturalistic design, we analyzed trauma- and intervention-related data of the sample (n = 377, 55.4% female, mean age 10.95, SD = 4.69). Following drop-out analyses, predictors for treatment outcome were identified by logistic regression. The majority (81.9%) was suffering from posttraumatic stress disorder (PTSD) or adjustment disorders. Around one forth dropped out of treatment; these cases showed higher avoidance symptoms at presentation. In 91%, psychological symptoms improved. Experience of multiple traumatic events was the strongest predictor for poor treatment outcome (B = −0.823, SE = 0.313, OR = 0.439, 95% CI 0.238-0.811). Around two thirds were connected to follow-up treatment. The OTC realized a high retention rate, initial improvement of symptoms and referral to subsequent longer-term psychotherapeutic treatment in the majority. Further dissemination of comparable early intervention models is needed, in order to improve mental health care for this vulnerable group.